Overexpressed NLRC3 Acts as an Anti-Inflammatory Cytosolic Protein - Gültekin, Yetiş (J Innate Immun, 2014)
The novel nucleotide oligomerization domain (NOD)-like receptor (NLR) with a caspase activation and recruitment domain (CARD) 3 (NLRC3) protein belongs to the NLR family of cytosolic pathogen recognition receptors. NLRC3 has the characteristic NOD and leucine-rich repeat configuration with a less well defined CARD. T lymphocytes are known to have high NLRC3 expression, which may be involved in suppression of T cell activation. Here, we report that NLRC3 is a cytoplasmic protein that negatively regulates pro-IL-1β maturation. Among well-known inflammasome components, NLRC3 can interact with apoptosis-associated speck-like protein containing a CARD (ASC) and caspases 1 and 5. Transient transfection of NLRC3 into stable EGFP-ASC-expressing HEK293FT cells reduces NLR family, pyrin domain-containing 3 (NLRP3)/cryopyrin-induced formation of ASC specks in a dose- and time-dependent manner. This suggests that NLRC3 can regulate ASC speck formation, caspase-1 activation and IL-1β maturation. We show for the first time that inflammasome-like complexes assemble when caspase-1 and ASC are cotransfected together with NLRC3 in HEK293FT cells. However, overexpression of NLRC3 with NLRP3/cryopyrin inflammasome components suppresses pro-caspase-1 cleavage and IL-1β processing. Our study suggests that NLRC3 negatively regulates inflammatory responses.